Cardiac abnormalities in dogs with visceral leishmaniasis - Soares, Nicolle Pereira; Medeiros, Alessandra Aparecida; Mundim, Antônio Vicente; Magalhães, Geórgia Modé; Sousa, Marcus Vinícius Caetano; Viadanna, Pedro Henrique de Oliveira (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Soares N.P., Medeiros A.A., Mundim A.V., Magalhães G.M., Souza M.V.C. & Viadanna P.H.O. [Cardiac abnormalities in dogs with visceral leishmaniasis.] Alterações cardíacas em cães com leishmaniose visceral. Revista Brasileira de Medicina Veterinária, 37(4):339-344, 2015. Laboratório de Patologia Animal, Hospital Veterinário, Faculdade de Medicina Veterinária, Universidade Federal de Uberlândia, Av. Ceará, s/n, Bloco 2T, Campus Umuarama, Uberlândia, MG 38400-902, Brasil. E-mail: nicolle.pereira@hotmail.com Canine visceral leishmaniasis (CVL) is a chronic disease, endemic and multisystemic, plus a zoonosis. The infected dog may develop various symptoms affecting multiple systems, including the cardiovascular system. For this reason, we used 43 animals positive for leishmaniasis in order to identify the macro and microscopic alterations of the myocardium and relate them to the levels of the enzyme creatine kinase (CK) and Total CK-MB isoenzyme in serum. On macroscopic examination revealed a dilation of the cardiac chambers, thickening of the muscles of the left ventricle with narrowed lumen and thinning of the right ventricular wall with increased chamber. Histologically, the most frequent findings were coagulation necrosis, myofibrillar degeneration and myocarditis. The CK values ranged from 20 to 1236.4 U / L with an average of 263.31 U / L for CK-MB while the average was 937.34 U / L, ranging from 234.94 U / L to 5477, 83U / L, both above the levels established for the canine species. The CK analyzed together with CK-MB isoenzyme are sensitive indicators for muscle injury in humans and domestic animals. Thus, in seropositive dogs, Leishmania causes nonsuppurative linfoplasmocitic myocarditis, myocardial necrosis, accompanied by an increase in the CK and CK-MB.